Dielectric, copper-clad laminate, and production methods therefor
Patent Information
- Application Number
- JP2024191672
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-10-04
- Filing Date
- 2024-10-31
- Publication Date
- 2025-04-15
AI Technical Summary
【0014】 本開示の誘電体は、低誘電率及び低損失であり、電気特性に優れ、また、本開示の誘電体を用いて銅張積層体を製造した際に、銅箔の膨れが発生しない。
Abstract
Description
[Technical field]
[0001] FIELD OF THE DISCLOSURE This disclosure relates to dielectrics, copper clad laminates and methods for their manufacture. [Background technology]
[0002] There is a demand for high-frequency printed wiring boards with small transmission loss. Patent documents 1 to 3 describe the use of fluororesin containing a filler as a wiring board material for such high-frequency printed wiring boards. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 63-259907 [Patent Document 2] International Publication No. 2021 / 024883 [Patent Document 3] International Publication No. 2021 / 235460 Summary of the Invention [Problem to be solved by the invention]
[0004] The present disclosure aims to provide a dielectric having excellent electrical properties and free from copper foil blistering during the manufacture of a copper clad laminate using the dielectric, and a method for manufacturing the same. Another aim of the present disclosure is to provide a copper clad laminate using the dielectric, and a method for manufacturing the same. [Means for solving the problem]
[0005] The present disclosure relates to a dielectric material having a moisture content of 1000 μg / g or less. The dielectric material preferably contains a resin and an inorganic filler.
[0006] The resin is preferably a fluororesin. The fluororesin is preferably non-melt processable. The fluororesin is preferably made of polytetrafluoroethylene (PTFE) in whole or in part. The polytetrafluoroethylene preferably has a standard specific gravity (SSG) of 2.0 to 2.3.
[0007] The inorganic filler is preferably at least one selected from the group consisting of silica, titanium oxide, magnesium oxide, alumina, and forsterite. The inorganic filler is preferably composed of silica in part or in whole. The content of the silica relative to the total amount of the dielectric is preferably 30 mass % or more. It is preferable that the resin is polytetrafluoroethylene (PTFE), the filler is silica, and the content of the silica relative to the total amount of the dielectric is 50% by mass or more and 70% by mass or less.
[0008] The average particle size of the silica is preferably 0.2 to 10 μm. The silica is preferably one whose surface is coated with a silane coupling agent.
[0009] It is preferable that the fluororesin is in the form of particles, and the average particle size is 0.05 to 1000 μm.
[0010] The present disclosure also relates to a metal clad laminate having the dielectric material and a metal foil. The present disclosure is also a copper clad laminate having the dielectric and a copper foil. It is preferable that the surface roughness Rz of at least the surface of the copper foil that is to be bonded to the dielectric is 2.0 μm or less. The copper foil is preferably rolled copper or electrolytic copper.
[0011] The dielectric material preferably has a dielectric loss tangent value of 0.0015 or less at 10 GHz. The dielectric material preferably has a thickness of 5 to 250 μm.
[0012] The present disclosure also relates to a method for producing the dielectric material, characterized in that a film is formed by mixing fluororesin particles and an inorganic filler. In the above-mentioned production method, it is preferable that the film is formed using a composition substantially consisting of fluororesin particles and an inorganic filler.
[0013] The present disclosure also relates to a method for producing the copper clad laminate, which comprises laminating a dielectric and a copper foil, heating the laminate at a temperature in the range of 180 to 390°C, and press-molding the laminate at a pressure in the range of 1 to 100 kN under vacuum or in an inert gas atmosphere. The present disclosure also relates to a circuit board comprising the dielectric or the copper clad laminate. Effect of the Invention
[0014] The dielectric of the present disclosure has a low dielectric constant and low loss, and is excellent in electrical properties. Furthermore, when a copper clad laminate is produced using the dielectric of the present disclosure, no blistering of the copper foil occurs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present disclosure will be described in detail below. In the field of high-frequency printed wiring boards, increasingly high levels of performance, such as low dielectric constant and low loss, are being required in recent years. On the other hand, many studies have been conducted on dielectric materials that contain fillers in resins such as fluororesins.
[0016] The present disclosure provides a dielectric having excellent electrical properties that satisfy the requirements of low dielectric constant and low loss by setting the moisture content of the dielectric within a specific range, and which does not cause blistering of the copper foil when a copper-clad laminate is manufactured using the dielectric.
[0017] When the moisture content in the dielectric is too high, the electrical properties of the dielectric deteriorate. A copper clad laminate containing such a dielectric has a large transmission loss, and is therefore unsuitable as a copper clad laminate. In addition, when a dielectric is produced by powder rolling molding using silica with a relatively small particle size as a filler, the amount of water absorption is found to be large. When a copper clad laminate is produced using such a dielectric with a large moisture content, blisters occur in the copper foil. In Patent Documents 1 to 3, the use of a hydrophobic filler and the reduction of voids in the dielectric are considered in order to reduce the moisture content. However, Patent Documents 1 to 3 do not disclose the specific moisture content of the dielectric layer of the copper clad laminate, and thus far, the appropriate moisture content in the dielectric has not been fully considered.
[0018] The present disclosure is directed to finding an optimal amount of moisture contained in a dielectric. The dielectric of the present disclosure is characterized in that the moisture content is 1000 μg / g or less. The moisture content of the dielectric is preferably 500 μg / g or less, and more preferably 400 μg / g or less.
[0019] In the present disclosure, the above water content is a value measured by the following method. The dielectric materials are cut to a size (40 mm x 50 mm) that can fit into the boat of the device, and then placed in the vaporization chamber of a moisture measuring device (CA-200, VA-200, manufactured by Mitsubishi Chemical Corporation) to measure the moisture generated at 250°C under the following conditions. Electrolyte: Hydranal Coulomat AG-OVEN Hydranal CG Vaporization chamber temperature condition: 250℃ Vaporizer nitrogen flow rate: 250mL / min
[0020] In the present disclosure, the lower limit of the moisture content of the dielectric is preferably 50 μg / g, more preferably 100 μg / g, and even more preferably 150 μg / g. If the moisture content in the dielectric is too low, it may be difficult to control the film formation conditions and to maintain the dielectric sheet shape.
[0021] In the present disclosure, the dielectric for which the moisture content is to be measured may be a dielectric obtained by etching the copper foil of a copper clad laminate in which a dielectric and a copper foil are laminated together.
[0022] The dielectric of the present disclosure is made of a resin. In the case of a fluororesin, the dielectric of the present disclosure preferably contains an inorganic filler.
[0023] (resin) The resin is preferably at least one selected from the group consisting of fluororesin, polyimide, modified polyimide, liquid crystal polymer (LCP), polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, and polybutadiene. The dielectric material of the present disclosure preferably contains a fluororesin, which has low dielectric properties and can therefore be suitably used for the purposes of the present disclosure.
[0024] (Fluorine resin) The fluororesin used in the present disclosure is preferably in particulate form. The average particle size of the fluororesin particles is preferably 0.05 to 1000 μm. The lower limit of the average particle size of the fluororesin particles is more preferably 0.07 μm or more, and even more preferably 0.1 μm or more. The upper limit of the average particle size of the fluororesin particles is preferably 700 μm or less, and even more preferably 500 μm or less. The use of such a material has the advantage of excellent moldability and dispersibility. The average particle size here is a value measured in accordance with ASTM D 4895.
[0025] The fluororesin particles preferably have a volume-based cumulative 50% diameter of 0.05 to 40 μm. The lower limit of the volume-based cumulative 50% diameter of the fluororesin particles is more preferably 0.7 μm or more, and even more preferably 1 μm or more. The upper limit of the volume-based cumulative 50% diameter of the fluororesin particles is preferably 35 μm or less, and even more preferably 30 μm or less. The use of such a material has the advantage of excellent moldability and dispersibility. The volume-based cumulative 50% diameter here is a value measured by a laser diffraction particle size distribution analyzer.
[0026] The fluororesin particles used in the present disclosure are not particularly limited, and examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene [CTFE] copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], tetrafluoroethylene having a molecular weight of 300,000 or less [LMW-PTFE], etc. One type may be used, or two or more types may be mixed.
[0027] The fluororesin particles used in the present disclosure are preferably non-melt processable. Being non-melt processable means that the resin does not have sufficient fluidity even when heated above its melting point, and cannot be molded by melt molding techniques commonly used for resins. PTFE falls into this category. In addition, from the viewpoint of low dielectric properties, PTFE is particularly preferable. PTFE having fibrillation properties is preferable. PTFE having fibrillation properties means PTFE in which unsintered polymer particles can be paste extruded or powder roll molded.
[0028] The fluororesin is preferably partially or entirely made of PTFE.
[0029] PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), homopolytetrafluoroethylene (hereinafter referred to as homoPTFE), or a mixture of modified PTFE and homoPTFE. From the viewpoint of maintaining good moldability of polytetrafluoroethylene, the content of modified PTFE in the polymeric PTFE is preferably 10% by weight or more and 98% by weight or less, and more preferably 50% by weight or more and 95% by weight or less. The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.
[0030] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE may be, but is not limited to, one that is uniformly modified by the modified monomer, one that is modified at the beginning of the polymerization reaction, one that is modified at the end of the polymerization reaction, etc. The modified PTFE is preferably a TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE within a range that does not significantly impair the properties of the TFE homopolymer. The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.
[0031] The modified PTFE contains TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500 mass% of the total monomer units, more preferably 0.01 to 0.30 mass%. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.
[0032] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.
[0033] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF2 = CF-ORf (1) (In the formula, Rf represents a perfluoro organic group.)
[0034] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.
[0035] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE) in which Rf in the above general formula (1) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group. Preferred examples of PAVE include perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).
[0036] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.
[0037] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.
[0038] The PTFE used in the present disclosure may have a core-shell structure.The PTFE having a core-shell structure may include, for example, modified polytetrafluoroethylene, which contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in a particle.As such modified polytetrafluoroethylene, for example, the polytetrafluoroethylene described in JP-A-2005-527652 may be included.
[0039] In the present disclosure, it is preferable to use such a non-melt-processable fluororesin and form it into a fluororesin sheet by a molding method that fibrillates the fluororesin. The molding method will be described later.
[0040] The PTFE preferably has a standard specific gravity (SSG) of 2.0 to 2.3. When such PTFE is used, a PTFE membrane having high strength (cohesion and puncture strength per unit thickness) is easily obtained. PTFE having a large molecular weight has a long molecular chain, and therefore it is difficult to form a structure in which the molecular chains are regularly arranged. In this case, the length of the amorphous part increases, and the degree of entanglement between the molecules increases. When the degree of entanglement between the molecules is high, the PTFE membrane is unlikely to deform under an applied load and is considered to exhibit excellent mechanical strength. In addition, when a PTFE having a large molecular weight is used, a PTFE membrane having a small average pore size is easily obtained.
[0041] The lower limit of the SSG is more preferably 2.05, and even more preferably 2.1.The upper limit of the SSG is more preferably 2.25, and even more preferably 2.2.
[0042] Standard specific gravity (SSG) was measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.
[0043] The PTFE preferably has a refractive index in the range of 1.2 to 1.6. By having such a refractive index, it is preferable in terms of low dielectric constant. The refractive index can be adjusted to be within the above range by a method of adjusting the polarizability or flexibility of the main chain. The lower limit of the refractive index is more preferably 1.25, more preferably 1.30, and most preferably 1.32. The upper limit of the refractive index is more preferably 1.55, more preferably 1.50, and most preferably 1.45. The refractive indexes are values measured using a refractometer (Abbemat 300).
[0044] In this embodiment, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE particles is, for example, in the range of 2 million to 12 million. The lower limit of the molecular weight of the PTFE may be 3 million or 4 million. The upper limit of the molecular weight of the PTFE may be 10 million.
[0045] The number average molecular weight of PTFE can be measured by a method based on standard specific gravity and a method based on dynamic viscoelasticity when melted. The method based on standard specific gravity can be performed by a water displacement method based on ASTM D-792 using a sample molded based on ASTM D-4895 98. The method based on dynamic viscoelasticity is described, for example, by S. Wu in Polymer Engineering & Science, 1988, Vol. 28, 538 and the same document, 1989, Vol. 29, 273.
[0046] The particulate PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. By containing PTFE having a secondary particle diameter of 500 μm or more within this range, it is advantageous in that a composite sheet with high strength can be produced. By using PTFE with a secondary particle size of 500 μm or more, a composite sheet with lower resistance and excellent toughness can be obtained.
[0047] The lower limit of the secondary particle diameter is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.
[0048] The particulate PTFE preferably has an average primary particle size of 50 nm or more, more preferably 100 nm or more, even more preferably 150 nm or more, and particularly preferably 200 nm or more, in order to obtain a dielectric sheet having higher strength and excellent homogeneity. The larger the average primary particle diameter of PTFE, the more suppressed the increase in paste extrusion pressure when the powder is used for paste extrusion molding, and the better the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization process, it is preferably 350 nm.
[0049] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, measuring the above transmittance for the aqueous dispersion to be measured, and then based on the calibration curve.
[0050] The PTFE preferably has a maximum endothermic peak temperature (crystalline melting point) of 340±7°C.
[0051] The PTFE may be a low-melting-point PTFE having a maximum peak temperature of 338°C or lower on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter, or a high-melting-point PTFE having a maximum peak temperature of 342°C or higher on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter.
[0052] The low-melting-point PTFE particles are particles produced by emulsion polymerization, and have the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.08 to 2.2, and a dielectric tangent (tan δ) of 1.9×10 -4 ~4.0×10 -4 Examples of commercially available products include Polyflon fine powders F201, F203, F205, F301, and F302 manufactured by Daikin Industries, Ltd., CD090 and CD076 manufactured by Asahi Glass Co., Ltd., and TF6C, TF62, and TF40 manufactured by DuPont.
[0053] The high melting point PTFE particles are also produced by emulsion polymerization, and have the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tanδ) of 1.6×10 -4 ~2.2×10 -4 As commercially available products, for example, Polyflon Fine Powder F104 manufactured by Daikin Industries, Ltd., CD1, CD141, and CD123 manufactured by Asahi Glass Co., Ltd., and TF6 and TF65 manufactured by DuPont can be mentioned.
[0054] The average particle size of the secondary aggregate particles of both PTFE particles is usually preferably 250 to 2000 μm. In particular, granulated particles obtained by granulation using a solvent are preferred from the viewpoint of improving the flowability when filling a mold during preforming.
[0055] PTFE having a particle shape that satisfies the above-mentioned parameters can be obtained by a conventional manufacturing method. For example, it may be manufactured according to the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.
[0056] (Inorganic filler) The inorganic filler that can be used in the present disclosure is not particularly limited, and examples thereof include inorganic fillers that are one or more types selected from ceramics, talc, mica, alumina, zinc oxide, tin oxide, titanium oxide, silicon oxide, calcium carbonate, calcium oxide, magnesium oxide, potassium titanate, forsterite, glass fiber, glass chips, glass beads, silica, calcium fluoride, boron nitride, barium sulfate, molybdenum disulfide, and potassium carbonate whiskers. Two or more types of these may be used in combination. Among these, it is particularly preferable that the inorganic filler is at least one selected from the group consisting of silica, titanium oxide, magnesium oxide, alumina, and forsterite. Or, it is preferable that the inorganic filler contains a combination of these. In particular, it is preferable that the inorganic filler is partly or entirely silica.
[0057] The inorganic filler is not particularly limited in shape, and examples thereof include a spherical shape, a crushed shape, etc. Among these, a spherical shape is preferable. A spherical shape is preferable in that it is easy to process uniformly during hole drilling, has a small specific surface area, and has low transmission loss.
[0058] The spherical inorganic filler means that the particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is calculated by taking a photograph with an SEM and calculating the value from the area and perimeter of the observed particle as (sphericity) = {4π x (area) ÷ (perimeter) 2}. The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.
[0059] In the present disclosure, the inorganic filler preferably has an average particle size of 0.1 to 10 μm. The average particle size here is the D50 value measured by a laser diffraction particle size distribution analyzer. If the average particle size is less than 0.1 μm, the inorganic filler tends to aggregate, making it difficult to obtain a sufficient effect. If the average particle size exceeds 10 μm, the sheet tends to be difficult to form into a thin film. The lower limit of the average particle size is more preferably 0.2 μm, and the upper limit of the average particle size is more preferably 5 μm.
[0060] The silica particles used in the present disclosure preferably have an average particle size of 0.2 to 10 μm. If the average particle size is less than 0.2 μm, the silica particles tend to absorb a large amount of water. If the average particle size is more than 10 μm, the sheet tends to be difficult to form into a thin film. The lower limit of the average particle size is more preferably 0.3 μm, and even more preferably 0.4 μm.The upper limit of the average particle size is more preferably 5 μm, and even more preferably 3 μm.
[0061] In addition, the spherical silica particles used in the present disclosure preferably have a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is accumulated from the smallest particle diameter. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). Since the small particle diameter spherical silica particles can enter the gaps between the large particle diameter spherical silica particles, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a higher frequency on the side of small particle diameters compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. It is also preferable that the coarse particles having a particle size of a predetermined size or more are removed by a filter or the like.
[0062] The above-mentioned spherical silica preferably has a water absorption of 1.0% or less, more preferably 0.5% or less. The water absorption is based on the mass of the spherical silica when dry. The water absorption is measured by leaving a sample in a dry state at 40°C and 80% RH for 1 hour, and measuring the water generated by heating at 200°C using a Karl Fischer water content meter, and then calculating the water absorption.
[0063] The above-mentioned spherical silica can also be measured for each of the parameters by heating the dielectric sheet at 600° C. for 30 minutes in an air atmosphere to burn off the fluororesin and extracting the spherical silica particles.
[0064] The spherical silica may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), and Admafuse (manufactured by Admatechs Co., Ltd.).
[0065] The titanium oxide, magnesium oxide, and alumina have a higher dielectric constant (Dk) than silica, and can be added to adjust the dielectric constant (Dk). Commercially available titanium oxide includes CR-EL (manufactured by Ishihara Sangyo Kaisha, Ltd.) and HT0210 (manufactured by Toho Titanium Co., Ltd.). Commercially available magnesium oxide includes RF-10CS and RF-10C-45μm (manufactured by Ube Material Industries, Ltd.). Commercially available alumina includes LS-110F and LS-210B (manufactured by Nippon Light Metal Co., Ltd.).
[0066] The inorganic filler, particularly the silica particles, is preferably surface-treated. By previously subjecting the inorganic filler to a surface treatment, aggregation of the inorganic filler, particularly the silica particles, can be suppressed, and the inorganic filler, particularly the silica particles, can be well dispersed in the resin composition.
[0067] The above surface treatment can be carried out by appropriately selecting the type and amount of a surface treatment agent. The surface treatment is not particularly limited, and any known treatment can be used.Specific examples of the surface treatment include treatment with a silane coupling agent such as epoxysilane, aminosilane, isocyanatesilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.
[0068] Specific examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, isocyanate silanes such as 3-isocyanatepropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane.
[0069] In the present disclosure, among the surface-treated silica particles, it is preferable to use silica particles whose surfaces are coated with a silane coupling agent. By performing an appropriate surface treatment, the water absorption amount of silica can be reduced.
[0070] When treating with a silane coupling agent, the amount of the silane coupling agent is preferably 3% by mass or less relative to the inorganic filler, particularly silica particles. When the amount of the silane coupling agent is large, the inorganic filler, particularly silica particles, absorbs a large amount of water, and when a dielectric is produced by powder rolling molding, many cracks occur in the dielectric. As a result, the moisture content of the dielectric increases, and the copper foil tends to blister when a copper clad laminate is produced.
[0071] (Dielectric) The dielectric of the present disclosure is made of resin, and preferably contains the above-mentioned inorganic filler and fluororesin particles. If necessary, it may contain components other than the inorganic filler and fluororesin particles, or may be composed only of the inorganic filler and fluororesin particles. The content of components other than the inorganic filler and fluororesin particles is preferably 10 mass% or less with respect to the total amount of the dielectric. In particular, it is preferable for the dielectric to be substantially composed of fluororesin particles and inorganic filler. Here, "substantially composed of fluororesin particles and inorganic filler" means that the content of components other than the inorganic filler and fluororesin particles is 3 mass % or less with respect to the total amount of the dielectric.
[0072] The content of the inorganic filler relative to the total amount of the dielectric is preferably 30% by mass or more. Within this range, the linear expansion coefficient of the dielectric can be controlled to be low. The content of silica relative to the total amount of the dielectric is preferably 30 mass % or more. The lower limit of the content of the inorganic filler is more preferably 35% by mass, and even more preferably 40% by mass, while the upper limit of the content of the inorganic filler is preferably 70% by mass.
[0073] The dielectric material of the present disclosure is usually used in the form of a sheet. The dielectric preferably has a thickness of 5 to 250 μm. The dielectric of the present disclosure can sufficiently achieve its purpose even if it is thin. From this viewpoint, the thickness is more preferably less than 200 μm, and further preferably less than 150 μm.
[0074] The dielectric of the present disclosure preferably has a 10 GHz dielectric loss tangent (Df) of 0.0015 or less. Having the dielectric within this range is preferable in that the dielectric loss is low. The upper limit of the dielectric loss tangent (Df) is more preferably 0.0012, and further preferably 0.0011. On the other hand, the lower limit of the dielectric loss tangent (Df) is preferably 0.00001.
[0075] The dielectric of the present disclosure preferably has a relative dielectric constant (Dk) of 3.5 or less at 10 GHz. Having the dielectric within this range is preferable in that the dielectric loss is low. The upper limit of the relative dielectric constant (Dk) is more preferably 3.2, and even more preferably 3.1, while the lower limit of the relative dielectric constant (Dk) is preferably 2.0, and more preferably 2.5.
[0076] In this specification, the relative permittivity (Dk) and dielectric loss tangent (Df) at 10 GHz were determined by measuring Dk and Df at 25° C. and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab).
[0077] Also, the coefficient of linear expansion (CTE) is preferably 100 ppm / K or less. By setting it within such a range, it is preferable to obtain a dielectric sheet with low shrinkage and excellent dimensional stability. The upper limit of the coefficient of linear expansion (CTE) is more preferably 70 ppm / K, and even more preferably 50 ppm / K. On the other hand, the lower limit of the coefficient of linear expansion (CTE) is more preferably 5 ppm / K, and even more preferably 10 ppm / K.
[0078] The linear expansion coefficient in this specification was determined by performing TMA measurement in a tensile mode using a TMA-7100 (manufactured by Hitachi High-Tech Science Corporation), using a sheet cut to a length of 20 mm and a width of 5 mm as a sample piece, setting the chuck distance to 10 mm, and determining the linear expansion coefficient from the amount of displacement of the sample at 0 to 150°C with a heating rate of 2°C / min while applying a load of 49 mN.
[0079] (Method of manufacturing dielectric material) The dielectric of the present disclosure can be obtained by mixing the above-mentioned fluororesin particles and inorganic filler to form a film. The present disclosure also relates to a method for producing a derivative by mixing the fluororesin particles and inorganic filler to form a film. The manufacturing method is not limited, but can be performed by paste extrusion molding, powder rolling molding, etc. Among them, it is preferable to perform it by paste extrusion molding.
[0080] As described above, it is preferable to use a non-melt processable fluororesin as the fluororesin used in the dielectric of the present disclosure. When using such a fluororesin, when molding it into a sheet, it is preferable to mold it by fibrillating particulate PTFE as a raw material.
[0081] The specific methods for paste extrusion molding and powder rolling molding are not particularly limited, but the general methods are described below.
[0082] (Paste extrusion molding) The method for producing the sheet may include a step (1a) of mixing fluororesin particles, for example, PTFE powder obtained by using a hydrocarbon surfactant, with an inorganic filler and an extrusion aid, a step (1b) of paste extrusion molding the mixture obtained, a step (1c) of rolling the extrudate obtained by extrusion molding, a step (1d) of drying the rolled sheet, and a step (1e) of firing the dried sheet to obtain a molded product. The paste extrusion molding can also be carried out by adding conventionally known additives such as pigments and fillers to the fluororesin particles.
[0083] The extrusion aid is not particularly limited, and generally known ones can be used, such as hydrocarbon oils.
[0084] In the step (1e) of sintering the dried sheet to obtain a green body, the sintering temperature is preferably 350° C. or higher and 380° C. or lower, and the sintering time is preferably 15 minutes or higher and 1 hour or shorter, in order to reduce the moisture content in the dielectric.
[0085] (Powder rolling molding) Powder rolling molding is a method in which a resin powder is fibrillated by applying a shear force to the resin powder, and then molded into a sheet shape. The method may include a step of subsequently firing the powder to obtain a molded body. More specifically, A step (1) of applying a shear force to a raw material composition containing fluororesin particles and a filler while mixing the raw material composition. A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. The manufacturing method may include the following. The method may further include a step (4) of firing the sheet-like material obtained above at 200 to 400° C. for 1 to 60 minutes. Additionally, step (2) may be omitted.
[0086] In step (4) of firing the sheet-like material at 200 to 400°C for 1 to 60 minutes, the firing temperature is preferably 350°C or higher and 380°C or lower, and the firing time is preferably 15 minutes or higher and 1 hour or shorter, in order to reduce the moisture content in the dielectric.
[0087] When a sheet is produced by the above powder rolling molding method, it is preferable to form a film using a composition substantially consisting of fluororesin particles and an inorganic filler. Alternatively, it is preferable to mix only the fluororesin particles and the inorganic filler and then mold the mixture.
[0088] (Other resins) Examples of the liquid crystal polymer (LCP) include thermoplastic liquid crystal polyesters and thermoplastic liquid crystal polyesteramides having amide bonds introduced therein. The liquid crystal polymer may also be a polymer having isocyanate-derived bonds such as imide bonds, carbonate bonds, carbodiimide bonds, and isocyanurate bonds introduced into aromatic polyesters or aromatic polyesteramides. Polymers having a rigid structure such as naphthoic acid are also preferred.
[0089] Polyimide is a general term for polymers containing imide bonds in the repeating units, and may usually be an aromatic polyimide in which aromatic compounds are directly linked through imide bonds. Modified polyimide is a polymer containing imide bonds in the repeating unit, which reduces the water absorption of polyimide. Polyphenylene sulfide is a crystalline thermoplastic resin that has a simple linear structure in which benzene rings (p-phenylene groups) and sulfur atoms (sulfide bonds) are bonded alternately. Cycloolefin polymers are polymers that have a cyclic structure in the polymer chain, and can be produced by ring-opening metathesis polymerization or coordination polymerization.
[0090] Polystyrene is a polymer obtained by polymerizing styrene, and includes syndiotactic polystyrene in which the stereoregularity is controlled and crystallinity is imparted. Epoxy resin is a thermosetting synthetic resin with reactive epoxy groups at the terminals, the most representative of which is a copolymer of bisphenol A and epichlorohydrin. Various polyamines and acid anhydrides are used as curing agents. Bismaleimide resins are high-performance thermosetting addition-type polyimides that can be synthesized by condensing phthalic anhydride with an aromatic diamine in a 2:1 molar ratio to produce a bismaleimide, followed by Michael addition of more diamines to the terminal double bonds of the bismaleimide. Polyphenylene oxide is a thermoplastic resin made from 2,6-disubstituted phenols by oxidative coupling polymerization.
[0091] Polyphenylene ether (PPE) is a blend of polyphenylene oxide (PPO) and polystyrene, and is a resin that has strength and rigidity while also having impact resistance at low temperatures. Polyphenylene ether is a plastic that has characteristics such as heat resistance, flame retardancy, and chemical resistance. Modified polyphenylene ether is a general term for polymer alloys made by mixing polyphenylene ether (PPE), an amorphous engineering plastic, with other resins. The main chain has benzene rings bonded via ether bonds, making it a resin with excellent hydrolysis resistance. Polybutadiene is a type of general-purpose synthetic rubber made by the polymerization of 1,3-butadiene, and is a material with excellent elasticity, abrasion resistance, and low-temperature properties.
[0092] Examples of molding methods for sheets using resins other than the above-mentioned fluororesins include melt extrusion molding, cast molding, inflation molding, calendar molding, cast molding, vacuum / pressure molding, compression molding, press molding, etc. In each molding method, the moisture content can be reduced by controlling the molding temperature and molding time. In the case of a method for molding a sheet using a resin other than a fluororesin, it is preferable to mold the resin alone or a composition containing the resin and an inorganic filler.
[0093] (Thermal compression molding) The method for producing a liquid crystal polymer film preferably includes at least a heat treatment step in which a laminate in which both sides of a liquid crystal polymer film are sandwiched between a pair of heat-resistant releasable supports is subjected to heat treatment under a predetermined pressure at a temperature of (HT+15) to (HT+70)°C, where HT is the heat distortion temperature of the thermoplastic liquid crystal polymer film before the heat treatment step (hereinafter, sometimes referred to as HT), and a peeling step in which the pair of heat-resistant releasable supports is peeled off from the laminate to obtain a thermoplastic liquid crystal polymer film.
[0094] In the heat treatment process, a liquid crystal polymer film obtained by extrusion molding (e.g., inflation method, etc.) is used, and a laminate in which both sides of the liquid crystal polymer film are sandwiched between a pair of heat-resistant release supports is heat treated at a desired temperature under a desired pressure. Since the liquid crystal polymer molecules on the front and back sides present in the skin layer are subjected to shear force during this heat treatment, the liquid crystal polymer film after the heat treatment process can control the dielectric constant in the thickness direction to a desired range. In addition, the heat treatment process can also reduce the amount of moisture in the liquid crystal polymer. The heat-resistant releasable supports disposed on both sides of the liquid crystal polymer film may be of the same type or different types as long as the purpose can be achieved, but it is preferable that they are of the same type.
[0095] (Copper clad laminate) The dielectric material of the present disclosure can be used as a sheet for a circuit board by laminating it with other substrates.
[0096] The present disclosure also relates to a metal clad laminate having the above-mentioned dielectric and a metal foil. Examples of the metal include copper, stainless steel, aluminum, iron, silver, gold, ruthenium, etc. Furthermore, alloys of these metals can also be used. Among these, copper is preferred.
[0097] The present disclosure also relates to a copper clad laminate having the above-mentioned dielectric and copper foil. The copper clad laminate may be characterized in that copper foil is bonded to one or both sides of the above-mentioned dielectric. As described above, the dielectric containing the fluororesin of the present disclosure is particularly suitable for use in circuit board applications, and therefore can be suitably used as such a copper clad laminate.
[0098] The dielectric in the copper clad laminate preferably has a 10 GHz dielectric loss tangent (Df) of 0.0015 or less. By having it within such a range, it is preferable in terms of low dielectric loss. The upper limit of the dielectric loss tangent (Df) is more preferably 0.0012, and further preferably 0.0011. On the other hand, the lower limit of the dielectric loss tangent (Df) is preferably 0.00001.
[0099] The dielectric in the copper clad laminate preferably has a thickness of 5 to 250 μm. The dielectric of the present disclosure can sufficiently achieve its purpose even if it is thin. From this viewpoint, the thickness is more preferably less than 200 μm, and even more preferably less than 150 μm.
[0100] The copper foil preferably has a surface roughness Rz of 2.0 μm or less. That is, the dielectric of the present disclosure has excellent adhesion to copper foil having a high smoothness of Rz 2.0 μm or less. Furthermore, the copper foil only needs to have an Rz of 2.0 μm or less on at least the surface that is bonded to the dielectric, and the Rz value of the other surface is not particularly limited. The above Rz is the sum of the highest point (maximum peak height: Rp) and the deepest point (maximum valley depth: Rv). The above surface roughness is the ten-point average roughness defined in JIS-B0601. In this specification, the above Rz is a value measured using a surface roughness meter (product name: Surfcom 470A, manufactured by Tokyo Seiki Co., Ltd.) with a measurement length of 4 mm.
[0101] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm, and even more preferably in the range of 9 to 35 μm.
[0102] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0103] The copper foil having Rz of 2.0 μm or less is not particularly limited, and commercially available products can be used. Examples of commercially available copper foil having Rz of 2.0 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.) and electrolytic copper foil CF-V9S-SV-18 (thickness 18 μm / Rz 1.5 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.).
[0104] The copper foil may be surface-treated to enhance adhesive strength with the dielectric of the present disclosure.
[0105] The surface treatment is not particularly limited, but may be a silane coupling treatment, a plasma treatment, a corona treatment, a UV treatment, an electron beam treatment, etc., and the reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate, it is preferable to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but may be an alkoxy group such as a methoxy group or an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.
[0106] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.
[0107] The copper foil may have a roughening treatment layer on the surface thereof from the viewpoint of improving adhesion to a resin substrate. In addition, if there is a risk that the roughening treatment will degrade the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface can be reduced as necessary, or the roughening treatment can be omitted.
[0108] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.
[0109] The copper clad laminate of the present disclosure may further include layers other than the copper foil and the dielectric. The layers other than the copper foil and the dielectric are preferably layers made of at least one resin selected from the group consisting of polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, and polybutadiene.
[0110] The layers other than the copper foil and the dielectric are not particularly limited as long as they are made of the above-mentioned resins, and the thickness of the layers other than the copper foil and the dielectric is preferably within the range of 12.5 to 260 μm.
[0111] In the copper clad laminate of the present disclosure, the copper foil layer may be formed on one or both sides of the rolled sheet. Methods for forming the copper foil layer include laminating (adhering) copper foil to the surface of the rolled sheet, vapor deposition, plating, and the like. The method of laminating the copper foil includes a method using heat pressing. The heat pressing temperature can be from the melting point of the dielectric sheet -150°C to the melting point of the dielectric sheet +40°C. The heat pressing time is, for example, 1 to 30 minutes. The pressure of the heat pressing can be 0.1 to 10 MPa.
[0112] The present disclosure also relates to a method for producing a copper clad laminate, which comprises laminating a dielectric and a copper foil, heating the laminate at a temperature in the range of 180 to 390°C, and press-molding the laminate at a pressure in the range of 1 to 100 kN under vacuum or in an inert gas atmosphere. By performing press molding under such conditions, there is no deterioration of the dielectric and adhesion to copper foil is also possible.
[0113] The copper clad laminate of the present disclosure is not particularly limited in its application, and is suitably used as a circuit board. The present disclosure also relates to a circuit board having the dielectric or the copper clad laminate. A circuit board is a plate-shaped component for electrically connecting electronic components such as semiconductors and capacitor chips and simultaneously arranging and fixing them in a limited space. There is no particular limitation on the configuration of the circuit board formed from the derivative or copper clad laminate of the present disclosure. The circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The circuit board may be any of a single-sided board, a board, a double-sided board, and a multilayer board (such as a built-up board). In particular, it can be suitably used for flexible boards and rigid boards. In particular, it can be suitably used as a printed circuit board for high frequencies of 10 GHz or more.
[0114] There are no particular limitations on the method for producing the circuit board, and the circuit board can be produced by a general method using the above-mentioned copper clad laminate.
[0115] The dielectric and copper-clad laminate of the present disclosure are used as electric and electronic components, for example, antennas used in electronic devices and communication devices such as ETC, GPS, wireless LAN, and mobile phones, high-speed transmission connectors, CPU sockets, millimeter wave and quasi-millimeter wave radars such as collision prevention radars, RFID tags, capacitors, inverter parts, cable covering materials, insulating materials for secondary batteries such as lithium ion batteries, speaker diaphragms, etc.
[0116] Examples of high-speed communication compatible boards include base station antenna boards, antenna distribution boards, boards for RRH (Remote Radio Head) which is the radio part of a wireless base station, boards for the control part or baseband part (BBU: Base Band Unit) of a wireless base station, transceiver boards for high-speed communication, boards for RNC (Radio Network Controller), boards for high-speed transmitters, boards for high-speed receivers, boards for high-speed signal multiplexing circuits, boards for WiFig using the 60 GHz band, boards for data transfer used in servers for data centers, etc. Examples of high-speed communication compatible boards include antenna boards, for example, boards for massive multi-element antennas (Massive MIMO) for large-capacity communication required in standards after 5G.
[0117] The insulating film can be used not only as an insulator for circuit boards, but also as an insulator for signal line coating, for example, as an insulating coating material (e.g. insulating tube) for waveguides that transmit high-speed signals, QSFP cables for high-speed LANs, coaxial cables for high-speed communication (e.g. SFP+ cables, QSFP+ cables, etc.), and low-loss coaxial cables.
[0118] When using such high frequencies, materials used in electrical components such as connectors and communication devices such as casings are required to have stable electrical properties such as low relative dielectric constant (εr) and low dielectric tangent (tanδ). Insulating films can also be used as insulating materials for such materials.
[0119] The insulating film can also be used as an insulating material for connector printed wiring boards that require soldering. The insulator has excellent heat resistance, so problems are unlikely to occur even at high temperatures during soldering.
[0120] In dielectric waveguides, materials with low dielectric loss are required to transmit high frequency millimeter waves or submillimeter waves with low loss. Dielectric films can also be used as insulating materials for dielectric waveguides that transmit millimeter waves, submillimeter waves, etc. Examples of dielectric waveguides include cylindrical dielectric lines, rectangular dielectric lines, elliptical dielectric lines, tubular dielectric lines, image lines, insulator image lines, trapped image lines, rib guides, strip dielectric lines, inverted strip lines, H guides, and nonradiative dielectric lines (NRD guides).
[0121] The laminate for a circuit board is also a laminate having a copper foil layer, the above-mentioned dielectric, and a base layer. The base layer is not particularly limited, but preferably has a fabric layer made of glass fiber and a resin film layer.
[0122] The glass fiber fabric layer is a layer made of glass cloth, glass nonwoven fabric, or the like. The glass cloth may be commercially available, and is preferably treated with a silane coupling agent to enhance affinity with the fluororesin. The glass cloth may be made of E glass, C glass, A glass, S glass, D glass, NE glass, low dielectric constant glass, etc., and is preferably made of E glass, S glass, or NE glass because of its easy availability. The fiber may be woven in either plain or twill weave. The thickness of the glass cloth is usually 5 to 90 μm, and preferably 10 to 75 μm, but it is preferable to use a glass cloth thinner than the fluororesin film to be used.
[0123] The laminate may use a glass nonwoven fabric as a fabric layer made of glass fibers. The glass nonwoven fabric is a fabric in which short glass fibers are fixed with a small amount of a binder compound (resin or inorganic substance), or a fabric in which the shape is maintained by entangling short glass fibers without using a binder compound, and a commercially available product can be used. The diameter of the short glass fibers is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of the binder compound include resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, and inorganic substances such as silica compounds. The amount of the binder compound used is usually 3 to 15 mass % based on the short glass fibers. Examples of the material of the short glass fibers include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, and preferably 100 to 900 μm. In the present disclosure, the thickness of the glass nonwoven fabric refers to a value measured in accordance with JIS P8118:1998 using a digital gauge DG-925 (load 110 grams, face diameter 10 mm) manufactured by Ono Sokki Co., Ltd. In order to increase the affinity with the fluororesin, the glass nonwoven fabric may be treated with a silane coupling agent.
[0124] Since most nonwoven glass fabrics have a very high porosity of 80% or more, it is preferable to use one that is thicker than the dielectric sheet and compress it by pressure.
[0125] The glass fiber fabric layer may be a layer in which a glass cloth and a glass nonwoven fabric are laminated together, whereby the properties of the two fabrics are combined to obtain suitable properties. The glass fiber fabric layer may be in the form of a prepreg impregnated with a resin.
[0126] In the above laminate, the fabric layer made of glass fiber and the dielectric may be bonded at the interface, or the fabric layer made of glass fiber may be partially or entirely impregnated with the dielectric. Furthermore, a prepreg may be prepared by impregnating a fabric made of glass fiber with a fluororesin composition. The prepreg thus obtained may be further laminated with the dielectric of the present disclosure. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the dielectric of the present disclosure may be used.
[0127] The resin film used as the substrate layer is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include those containing epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable.
[0128] The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption coefficient, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.2 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and even more preferably 40 ppm / °C or less. The water absorption coefficient is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less. EXAMPLES
[0129] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.
[0130] (Examples 1 to 3, Examples 5 to 9, Example 11, and Example 13) (Paste extrusion molding) The fluororesin particles (PTFE) and silica were each weighed so that the silica content was the amount shown in Table 1, and mixed in a mixer in the presence of dry ice. The temperature during mixing was -10°C or lower. The resulting mixture was mixed with 18-23% oil (Isopar H) and aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed body was extruded at 40° C. and 50 mm / min to obtain an extrusion sample. The extruded sample was rolled with two rolls (roll gap: set to 500 to 80 μm) to obtain a sample with a film thickness of 125 μm. The sample was dried at 200° C. for 2 hours and fired at 360° C. for 20 minutes to obtain a dielectric sheet.
[0131] The fluororesin particles (PTFE) used in each example had the following properties. Average particle size: 500μm Apparent density: 460g / L Standard specific gravity: 2.17
[0132] In addition, as shown in Table 1, the silica used in each example was Admatechs' SC6500-SQ (average particle size 2.1 μm) as spherical silica, Admatechs' SC6500-SQ (average particle size 2.1 μm) surface-treated with 3-aminopropyltriethoxysilane (1% by mass treatment in Examples 3 to 5, 10, and 11, and 10% by mass treatment in Comparative Example 2), or Admatechs' SC2500-SQ (average particle size 0.5 μm), and Tatsumori's ZA-30 or Tatsumori's ZA-30 surface-treated with a mixture of phenyltrimethoxysilane and aminoethylaminopropyltrimethoxysilane in a ratio of 9:1 and 1% by mass treatment.
[0133] (Example 4, Example 12) (Powder rolling molding) The fluororesin particles (PTFE) and silica were weighed out in the proportions shown in Table 1 and stirred twice for 30 seconds at room temperature with a Wonder Crusher at memory number 6. The obtained powder was rolled with two rolls (roll gap: set to 100 μm, roll temperature: 100°C) to obtain a sample with a film thickness of 130 μm, and was fired at 360°C for 20 minutes to obtain a dielectric sheet.
[0134] (Comparative Example 1 to Comparative Example 2) (Powder rolling molding) The fluororesin particles (PTFE) and silica were each weighed out so that the silica content was the amount shown in Table 1, and the mixture was stirred at room temperature with a Wonder Crusher at setting 6 for 30 seconds twice. The resulting mixture was rolled with two rolls (roll gap: set to 100 μm, roll temperature: 100° C.) to obtain a sample with a film thickness of 130 μm, which was then fired at 360° C. for 15 minutes to obtain a dielectric sheet.
[0135] In Comparative Example 1, fine spherical silica particles (UFP-30 (average particle size 0.1 μm) manufactured by Denka Co., Ltd.) were used.
[0136] Each of the obtained dielectric sheets was evaluated based on the following criteria. [Moisture content] The dielectric sheets were each cut to a size (40 mm x 50 mm) that would fit into the boat of the apparatus, and placed in the vaporization chamber of a moisture measuring device (CA-200, VA-200, manufactured by Mitsubishi Chemical Corporation), and the moisture generated at 250°C was measured under the following conditions. Electrolyte: Hydranal Coulomat AG-OVEN Hydranal CG Vaporization chamber temperature condition: 250℃ Vaporizer nitrogen flow rate: 250mL / min
[0137] [Dk and Df] Dk and Df were measured at 25°C and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (EM Lab).
[0138] [CTE (Coefficient of Linear Expansion)] TMA measurements were performed in tensile mode using a TMA-7100 (Hitachi High-Tech Science Corporation). A sheet cut to a length of 20 mm and a width of 5 mm was used as a sample piece. The distance between the chucks was set to 10 mm, and the CTE (coefficient of linear expansion) was calculated from the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min while applying a load of 49 mN.
[0139] (Manufacturing of copper clad laminates) The dielectric sheets obtained in Examples 1 to 9, Examples 11 to 13, and Comparative Examples 1 and 2 were sandwiched between two sheets of electrolytic copper foil CF-V9S-SV-18 (thickness 18 μm / Rz 1.5 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.), heated at 360° C., press-molded under vacuum at a pressure of 15 kN for 5 minutes, and cooled to room temperature to obtain copper-clad laminates. Each of the obtained copper clad laminates was evaluated based on the following criteria.
[0140] [Appearance of copper clad laminate] A test piece of 100 mm x 100 mm was cut out from the prepared copper clad laminate and visually inspected. If one or more blisters were found, it was judged to have a blisters, and if no blisters were found, it was judged to be good. The results are shown in Table 1.
[0141] Example 10 The copper clad laminate of Example 5 was etched by the following method, and the moisture content of the recovered dielectric layer was measured. (etching) The copper foil of the copper-clad laminate was etched with an aqueous solution of ferric chloride, washed with running fresh water for 2 to 5 minutes, washed with distilled water, and dried in a thermostatic chamber at 80±3°C for approximately 60 minutes to recover the individual dielectric layers. The results are shown in Table 1.
[0142] Example 14 A copolymer of p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid (molar ratio: 70 / 30) was melt extruded and then blown into a thermoplastic liquid crystal polymer film having a melting point of 325°C, a heat distortion temperature of 280°C, and a thickness of 100 μm. A 100 μm thick polyimide film (linear expansion coefficient: thermal 16 ppm / K) was used as a heat-resistant, releasable support, and both sides of the obtained thermoplastic liquid crystal polymer film were sandwiched together with the MD and TD directions of the two polyimide films aligned in the same direction to form a laminate. After preheating in a vacuum hot press, the laminate was heat-treated at 330°C for 15 minutes under a pressure of 3 MPa. After the heat treatment, the laminate was cooled and removed, and the polyimide film was peeled off to obtain a dielectric sheet. The obtained dielectric sheets were evaluated based on the above criteria. The above dielectric sheet was sandwiched between two sheets of electrolytic copper foil CF-V9S-SV-18 (thickness 18 μm / Rz 1.5 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.), press-molded under vacuum at 170° C., 3 MPa, and for 60 minutes, and then cooled to room temperature to obtain a copper-clad laminate. Each of the obtained copper clad laminates was evaluated based on the above criteria. The results are shown in Table 1.
[0143] [Table 1]
[0144] From the above results, the dielectric of the present disclosure improves the appearance of copper clad laminates. [Industrial Applicability]
[0145] The dielectric material of the present disclosure can be particularly suitably used for high-frequency printed circuit boards.
Claims
1. A dielectric sheet for metal-clad laminates, characterized in that the sheet has a moisture content of 1000 μg / g or less, contains a resin and an inorganic filler, the inorganic filler being partially or entirely silica, and the silica having a surface coated with a silane coupling agent.
2. The dielectric sheet for a metal clad laminate according to claim 1 , wherein the resin is a fluororesin.
3. The dielectric sheet for metal clad laminates according to claim 2 , wherein the fluororesin is non-melt processable.
4. 4. The dielectric sheet for metal clad laminates according to claim 2, wherein the fluororesin is partly or entirely made of polytetrafluoroethylene (PTFE).
5. 5. The dielectric sheet for metal clad laminates according to claim 4, wherein the polytetrafluoroethylene (PTFE) has a standard specific gravity (SSG) of 2.0 to 2.
3.
6. 3. The dielectric sheet for metal clad laminates according to claim 1, wherein the content of said silica in the total amount of the dielectric sheet is 30 mass % or more.
7. 3. The dielectric sheet for metal clad laminates according to claim 1, wherein the average particle size of the silica is 0.2 to 10 μm.
8. 4. The dielectric sheet for metal clad laminates according to claim 2, wherein the fluororesin is in the form of particles having an average particle size of 0.05 to 1000 μm.
9. 2. The dielectric sheet for metal clad laminates according to claim 1, wherein the resin is polytetrafluoroethylene (PTFE), and the content of the silica relative to the total amount of the dielectric sheet is 50% by mass or more and 70% by mass or less.
10. A metal clad laminate comprising the dielectric sheet for metal clad laminates according to claim 1 and a metal foil.
11. A copper clad laminate comprising the dielectric sheet for metal clad laminates according to claim 1 and copper foil.
12. The copper clad laminate according to claim 11, wherein at least the surface of the copper foil which is bonded to the dielectric sheet of the metal clad laminate has a surface roughness Rz of 2.0 μm or less.
13. 12. The copper clad laminate according to claim 11, wherein the copper foil is rolled copper or electrolytic copper.
14. The copper clad laminate according to claim 11, wherein the dielectric tangent value at 10 GHz of the dielectric sheet for the metal clad laminate is 0.0015 or less.
15. The copper clad laminate according to claim 11, wherein the dielectric sheet for the metal clad laminate has a thickness of 5 to 250 μm.
16. 3. A method for producing the dielectric sheet for a metal clad laminate according to claim 2, comprising mixing fluororesin particles and an inorganic filler to form a film.
17. 17. The method for producing a dielectric sheet for a metal clad laminate according to claim 16, wherein the film is formed using a composition substantially consisting of fluororesin particles and an inorganic filler.
18. The method for producing a copper clad laminate according to claim 11, characterized in that a dielectric sheet for a metal clad laminate and a copper foil are laminated, heated at a temperature in the range of 180 to 390°C, and press-molded under a pressure in the range of 1 to 100 kN in a vacuum or in an inert gas atmosphere.
19. A circuit board comprising the dielectric sheet for metal clad laminate according to claim 1 or the copper clad laminate according to claim 11.